CONCEPTUAL ANALYSIS OF PROVERBS WITH THE SOMATIC COMPONENT “HEAD/BOSH” IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article is dedicated to the conceptual analysis of proverbs with the somatic component “head/bosh” in English and Uzbek languages. The study examines proverbs containing this somatic element and analyzes their semantic, structural, and linguocultural features. The article explores the meanings and metaphorical implications of proverbs with the “head/bosh” component, as well as their role in reflecting national mentality. Additionally, a comparative analysis of such proverbs in English and Uzbek is conducted to identify their similarities and differences. The results of the study serve as a theoretical and practical basis for linguistic research, translation studies, and cultural studies.